Superior Vena Cava Syndrome Due to Mediastinal Tuberculous Lymphadenitis - Jang, Jin Ho (Korean J Fam Med, 2017)
Superior vena cava (SVC) syndrome refers to a medical emergency resulting from compression of the SVC. It requires early diagnosis and treatment, and is usually caused by malignant tumors; rarely, mediastinal tuberculous lymphadenitis can cause SVC syndrome. Here, we present a case study of an immunocompetent 61-year-old woman who presented with acute onset SVC syndrome and was diagnosed with tuberculous lymphadenitis on thoracotomy; the symptoms resolved with anti-tuberculosis therapy. This unusual case highlights the importance of the differential diagnosis in patients presenting with acute onset SVC syndrome; a timely diagnosis and appropriate treatment lead to complete recovery.